The Ca2+/calmodulin‐dependent kinase kinase β‐AMP‐activated protein kinase‐α1 pathway regulates phosphorylation of cytoskeletal targets in thrombin‐stimulated human platelets. (June 2014) - Onselaer, M.‐B.; Oury, C.; Hunter, R. W.; Eeckhoudt, S.; Barile, N.; Lecut, C.; Morel, N.; Viollet, B.; Jacquet, L.‐M.; Bertrand, L.; Sakamoto, K.; Vanoverschelde, J.‐L.; et al.
Summary Background Platelet activation requires sweeping morphologic changes, supported by contraction and remodeling of the platelet actin cytoskeleton. In various other cell types, AMP‐activated protein kinase (AMPK) controls the phosphorylation state of cytoskeletal targets. Objective To determine whether AMPK is activated during platelet aggregation and contributes to the control of cytoskeletal targets. Results We found that AMPK‐α1 was mainly activated by thrombin, and not by other platelet agonists, in purified human platelets. Thrombin activated AMPK‐α1 ex vivo via a Ca2+/calmodulin‐dependent kinase kinase β (CaMKKβ)‐dependent pathway. Pharmacologic inhibition of CaMKKβ blocked thrombin‐induced platelet aggregation and counteracted thrombin‐induced phosphorylation of several cytoskeletal proteins, namely, regulatory myosin light chains (MLCs), cofilin, and vasodilator‐stimulated phosphoprotein (VASP), three key elements involved in actin cytoskeletal contraction and polymerization. Platelets isolated from mice lacking AMPK‐α1 showed reduced aggregation in response to thrombin, and this was associated with defects in MLC, cofilin and VASP phosphorylation and actin polymerization. More importantly, we show, for the first time, that the AMPK pathway is activated in platelets of patients undergoing major cardiac surgery, in a heparin‐sensitive manner. Conclusion AMPK‐α1 is activated by thrombin in human platelets. It controls the phosphorylation of key cytoskeletal targets and actin cytoskeletal remodeling during platelet aggregation.